Assisted reproductive technology in Europe, 2013: results generated from European registers by ESHRE. Issue 10 (28th August 2017) - ,; ,; Calhaz-Jorge, C; De Geyter, C; Kupka, M S; de Mouzon, J; Erb, K; Mocanu, E; Motrenko, T; Scaravelli, G; Wyns, C; Goossens, V; et al.
Abstract: STUDY QUESTION: Are there any changes in the treatments involving ART and IUI initiated in Europe during 2013 compared with previous years? SUMMARY ANSWER: An increase in the overall number of ART cycles resulting from a higher number of countries reporting data was evident, the pregnancy rates (PRs) in 2013 remained stable compared with those reported in 2012, the number of transfers with multiple embryos (3+) was lower than ever before yet the multiple delivery rates (DRs) remained unchanged, and IUI activity and success rates were similar to those of last years. WHAT IS KNOWN ALREADY: Since 1997, ART data in Europe have been collected and reported in 16 manuscripts, published in Human Reproduction . STUDY DESIGN, SIZE, DURATION: Retrospective data collection of European ART data by the European IVF-monitoring Consortium for ESHRE. Data for cycles between 1 January and 31 December 2013 were collected from National Registers, when existing, or on a voluntary basis by personal information. PARTICIPANTS/MATERIALS, SETTINGS, METHODS: From 38 countries (+4 compared with 2012), 1169 clinics reported 686 271 treatment cycles including 144 299 of IVF, 330 367 of ICSI, 154 712 of frozen embryo replacement (FER), 40 244 of egg donation (ED), 247 of IVM, 9791 of PGD/PGS and 6611 of frozen oocyte replacements. European data on intrauterine insemination using husband/partner's semen (IUI-H) and donor semen (IUI-D) were reported from 1095 IUI labs in 22 countries. A total of 175 467 IUI-H and 43 785 IUI-D cycles were included. MAIN RESULTS AND THE ROLE OF CHANCE: In 17 countries where all clinics reported to their ART register, a total of 374 177 ART cycles were performed in a population of around 310 million inhabitants, corresponding to 1175 cycles per million inhabitants (range, 235–2703 cycles per million inhabitants). For all IVF cycles, the clinical PRs per aspiration and per transfer were stable with 29.6% (29.4% in 2012) and 34.5% (33.8% in 2012), respectively. For ICSI, the corresponding rates also were stable with 27.8% (27.8% in 2012) and 32.9% (32.3% in 2012). In FER-cycles, the PR per thawing/warming increased to 27.0% (23.1% in 2012). In ED cycles, the PR per fresh transfer increased to 49.8% (48.4% in 2012), to 38.5% (35.9% in 2012) per thawed transfer, and to 46.4% for transfers after FOR (45.1% in 2012). The DRs after IUI remained stable at 8.6% (8.5% in 2012) after IUI-H and was slightly lower after IUI-D (11.1% versus 12.0% in 2012). In IVF and ICSI cycles, 1, 2, 3 and 4+ embryos were transferred in 31.4, 56.3, 11.5, and 1.0% of the cycles, respectively (corresponding numbers were 30.2, 55.4, 13.3 and 1.1% in 2012). The proportions of singleton, twin and triplet deliveries after IVF and ICSI (added together) were 82., 17.5 and 0.5%, respectively, resulting in a total multiple DR of 18.0% compared to 17.9% in 2012. In FER-cycles, the multiple DR was 12.8% (12.5% twins and 0.3% triplets), nearly the same as in 2012 (12.5, 12.2 and 0.3% respectively). Twin and triplet DRs associated with IUI cycles were 9.5%/0.6% and 7.5%/0.3%, following treatment with husband/donor semen, respectively. LIMITATIONS, REASONS FOR CAUTION: The method of reporting varies among countries, and registers from a number of countries have been unable to provide some of the relevant data such as initiated cycles and deliveries. As long as data are incomplete and generated through different methods of collection, the results should be interpreted with caution. WIDER IMPLICATIONS OF THE FINDINGS: The 17th ESHRE report on ART shows a continuing expansion of the number of treatment cycles in Europe, with more than 685 000 cycles reported in 2013 and an increasing contribution to birth rate in many countries. However, the need to improve and standardize the national registries, and to establish validation methodologies, remains manifest. STUDY FUNDING/COMPETING INTEREST(S): The study has no external funding; all costs are covered by ESHRE. There are no competing interests.